Corporate Sustainability and Wealth Distribution: Evidence from Brazil’s Corporate Sustainability Index - Paulo A. Lozano; Feni Agostinho; Arno P. Clasen; Cecília M. V. B. Almeida; Biagio F. Giannetti (Administrative Sciences)
The growing demand for sustainable business practices has led to the development of corporate sustainability assessment tools, with environmental, social, and governance (ESG) indicators becoming central to non-financial performance evaluation. These metrics increasingly influence investment decisions and corporate strategies. However, questions remain about whether sustainability practices have a measurable impact on economic value creation and distribution. This study investigates the causal relationship between corporate sustainability measured by the ISE-B3 index and stakeholder-oriented economic performance, specifically focusing on Distributed Added Value (DAV) and its main components. The analysis uses financial data from Brazilian companies listed in the ISE-B3 portfolios for the years 2022, 2023, and 2024. To address potential endogeneity, this study employs a panel data econometric approach using Instrumental Variables with Two-Stage Least Squares (IV-2SLS) as the primary estimation strategy, complemented by fixed and random effects models for robustness checks. The results indicate no statistically significant causal relationship between the ISE-B3 index and DAV or its components. The coefficient of ISE-B3 on DAV is −0.0006 (p = 0.896) in the IV-2SLS estimation, with similar non-significant results for all components. The models exhibit strong temporal dependence, with lagged dependent variable coefficients ranging from 0.8295 to 1.3578, reflecting the persistence of financial dynamics. These findings suggest that, within the Brazilian context, participation in the ISE-B3 index does not directly influence how companies create or distribute financial value to stakeholders. This study contributes to the literature by providing robust econometric evidence on the economic effects of corporate sustainability, offering a stakeholder-oriented perspective beyond the traditional shareholder-centric view.